Analisis Pengelolaan Pendapatan Dan Belanja Daerah - Muzzammil Ihza Mahendra; Haliah; Andi Kusumawati (CV. AFDIFAL MAJU BERKAH, 2023)
This research aims to find out and analyze how regional income and expenditure management is seen from the economic, efficiency and effectiveness levels of the Bantaeng Regency Government from the 2020-2022 Fiscal Year. The data source used is secondary data in the form of reports on the realization of regional income and expenditure budgets as well as other information related to the problems studied. The results of research and data analysis using quantitative descriptive analysis are used to describe how regional income and expenditure management uses value for money analysis from the economic, efficiency and effectiveness levels of the Bantaeng Regency Government from the 2020-2022 Fiscal Year. Measuring performance in managing the revenue and expenditure budget using value for money analysis concluded that the Bantaeng Regency Government for the 2020 - 2022 budget year had used the economic concept with an average of 90.02%, the efficiency concept with an average of 90.21%, and the concept of effectiveness with an average of 90.92%. Although the three financial performance indicators measured using value for money analysis show relatively good performance, they are still not perfect